Economic Results of Forage Species Choice in Crop–Livestock Integrated Systems - Vanessa Nunes Leal; Darliane de Castro Santos; Tiago do Prado Paim; Luizmar Peixoto dos Santos; Estenio Moreira Alves; Flavio Lopes Claudio; Guido Calgaro Junior; Patrick Bezerra Fernandes; Paulo Alexandre Perdomo Salviano (Agriculture, 2023)
Crop–livestock integrated production systems (CLISs) combine cash-crop production and forage production in succession. There are plenty of options of forage cultivars with differences in production aspects and seeds cost, and there is little information on how the choice of forage cultivar can affect the results of a CLIS. We hypothesized that different forage cultivars can have important economic impacts on production systems. Thus, we evaluated the two-year economic results of using three forage species in a CLIS: (1) Urochloa ruziziensis; (2) Megathyrsus maximus cv. BRS Zuri e; and (3) Megathyrsus maximus cv. BRS Tamani. The system was evaluated during 2018 and 2019 with no-tillage soybean (Glycine max) cultivation from November to March and grazing of cattle from May to August. The seed costs were, on average, USD 25.27 ha−1 for Ruziziensis grass, USD 39.97 ha−1 for Zuri guinea grass, and USD 64.13 ha−1 for Tamani guinea grass. Animal production varied from 96.4 to 147.5 kg of live weight per hectare per year and mean two-year soybean yields varied from 3849 to 4217 kg per hectare, both without differences between forage cultivars. However, the lowest values for animal and soybean yields were obtained with Ruziziensis grass, and the highest were obtained with Zuri grass. Thus, Zuri guinea grass presented a net income (NI) of USD 1039.87 ha−1 with an annual return on equity (ROE) equal to 11.19%, while Ruziziensis grass obtained an NI equal to USD 612.65 ha−1 with an ROE of 6.47%, demonstrating the economic impact of forage resource choice in CLISs. Therefore, the choice of forage cultivars adequate for the conditions of an individual farm can correspond to an increase of 69.7% in net income, which highlights the importance of continuing efforts to develop new cultivars and the simultaneous evaluation of these cultivars in different production scenarios in order to better recommend forage genetic resources for particular production environments.